2014
DOI: 10.1007/s11864-014-0280-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Advanced Squamous Cell Carcinoma of the Skin

Abstract: Advanced unresectable squamous cell carcinoma of the skin (SCCS) is a rare condition, which is difficult to treat. Because of its rarity, few therapeutic trials are available. Moreover, SCCS often occur in elderly. Conventional treatment options for advanced SCCS are chemotherapy mainly with cisplatin-based regimens. Immunotherapy with interferon alpha and retinoids combination was also shown to be efficient. Toxicity of these treatments limits, however, their use in elderly patients and an initial work up for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 86 publications
2
34
1
Order By: Relevance
“…Similar to BCCs, aSCCs are defined as tumours that are unresectable due to their location around critical structures, that is, ear, nose, orbital area, due to deep invasion of underlying structures such as bone, nerve or muscle or due to metastasis in regional lymph nodes or other distant areas [60]. Staging criteria of SCCs are summarized in Table 2.…”
Section: Treatment Of Asccsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to BCCs, aSCCs are defined as tumours that are unresectable due to their location around critical structures, that is, ear, nose, orbital area, due to deep invasion of underlying structures such as bone, nerve or muscle or due to metastasis in regional lymph nodes or other distant areas [60]. Staging criteria of SCCs are summarized in Table 2.…”
Section: Treatment Of Asccsmentioning
confidence: 99%
“…Cisplatin has been used in a number of combinations with mixed results. These include combinations with bleomycin, doxorubicin, 5-FU and bleomycin, and a combination of chemoradiation with 5-FU [60]. Guthrie et al reported encouraging results in two different studies, where a combination of cisplatin and doxorubicin was used [61,62].…”
Section: Conventional Treatments For Asccmentioning
confidence: 99%
See 3 more Smart Citations